Analisis Pengaruh Kinerja Keuangan Daerah terhadap Pertumbuhan Ekonomi di Kabupaten Kotabaru - Y Yayu; S Saipudin (PPJP Universitas Lambung Mangkurat, 2022)
This study aimed to determine the effect of the PAD effectivity ratio and APBD efficiency ratio on economic growth in the Kotabaru district. To answer the problem, Multiple Linear Regression Analysis is used. The data used in this study are secondary data on the budget realization report at constant prices based on business 2010 - 2018. The results of the research based on Multiple Linear Regression analysis show that the PAD effectivity ratio has a significant effect on economic growth in Kotabaru Regency, and APBD efficiency significant affects economic growth in the Kotabaru district.